A Weibull and finite mixture of the von Mises distribution for wind analysis in Mersing, Malaysia. Issue 12 (26th September 2017) - Sanusi, Nortazi; Zaharim, Azami; Mat, Sohif; Sopian, Kamaruzzaman
ABSTRACT: Studies of wind direction receive less attention than that of wind speed; however, wind direction affects daily activities such as shipping, the use of bridges, and construction. This research aims to study the effect of wind direction on generating wind power. A finite mixture model of the von Mises distribution and Weibull distribution are used in this paper to represent wind direction and wind speed data, respectively, for Mersing (Malaysia). The suitability of the distribution is examined by the R 2 determination coefficient. The energy analysis, that is, wind power density, only involves the wind speed, but the wind direction is vital in measuring the dominant direction of wind so that the sensor could optimize wind capture. The result reveals that the estimated wind power density is between 18.2 and 25 W/m 2, and SSW is the most common wind direction for this data.